Systemic Diseases and Biological Dental Implant Complications: A Narrative Review - Luca Sbricoli; Elissar Bazzi; Edoardo Stellini; Christian Bacci (MDPI AG, 2022)
The relationship between periodontitis and such systemic disorders as diabetes, cardiovascular disease and obesity has been extensively investigated. There is less scientific evidence available, however, regarding the influence of systemic diseases on the risk of late failure of dental implant rehabilitation due to peri-implantitis. The aim of the present study was to review the literature on the role of several common systemic disorders (diabetes, obesity, cardiovascular disease, hypertension and osteoporosis) in the onset of peri-implantitis. A database search initially yielded 2787 studies of potential interest published up to 1 March 2022 (993 in PubMed; 908 in Web of Science; and 886 in Scopus). After removing 1190 duplicate articles and checking the titles, abstracts and full texts for relevance, 70 articles were selected for the present analysis. Only cohort, case-control studies and clinical case series were considered. Most of the literature concludes for no association between diabetes, cardiovascular disease, hypertension or osteoporosis and the risk of peri-implantitis. On the other hand, almost all the studies that investigated obesity as a risk factor for implant rehabilitation found a positive association between the two. Further longitudinal studies are needed to better understand the effects of systemic diseases on rehabilitation with dental implants.